An industrial security system for human-robot coexistence. Issue 2 (19th March 2018) - Long, Philip; Chevallereau, Christine; Chablat, Damien; Girin, Alexis
Abstract : Purpose: The installation of industrial robots requires security barriers, a costly, time-consuming exercise. Collaborative robots may offer a solution; however, these systems only comply with safety standards if operating at reduced speeds. The purpose of this paper is to describe the development and implementation of a novel security system that allows human–robot coexistence while permitting the robot to execute much of its task at nominal speed. Design/methodology/approach: The security system is defined by three modes: a nominal mode, a coexistence mode and a gravity compensation mode. Mode transition is triggered by three lasers, two of which are mechanically linked to the robot. These scanners create a dynamic envelope around the robot and allow the detection of operator presence or environmental changes. To avoid velocity discontinuities between transitions, the authors propose a novel time scaling method. Findings: The paper describes the system's mechanical, software and control architecture. The system is demonstrated experimentally on a collaborative robot and is compared with the performance of a state-of-art security system. Both a qualitative and quantitative analysis of the new system is carried out. Practical implications: The mode transition method is easily implemented, requires little computing power and leaves the trajectories unchanged. As velocity discontinuities are avoided, motor wear is reduced. The execution time is substantially less than a commercial alternative. These advantages can lead to economic benefits in high-volume manufacturing environments. Originality/value: This paper proposes a novel system that is based on industrial material but can generate dynamic safety zones for a collaborative robot.